Cittadini of Venice : Shaping Identities between Networks and Patronage (c. 1530-1690) - Zanon, Giulia, (Art and Material Culture in Medieval and Renaissance Europe ;, 2024)
In this volume Giulia Zanon sheds new light on our grasp of social hierarchy and the possibilities for social mobility in pre-modern Italy. By adopting an interdisciplinary approach that combines deep archival research with a multitude of artistic and architectural artefacts, this work breaks new ground by contextualizing the part played by social relationships and the arts in publicly affirming and displaying the prestige of the middling sorts, the cittadini , in early modern Venice.